Diabetes-related posttraumatic stress symptoms, resilience, and illness management among adolescents and young adults with type 1 diabetes: an exploratory study - Hosoda-Urban, Tamaki; O’Donnell, Ellen (Frontiers in Psychiatry, 2025)
AimsThis study examined relationships between diabetes-related posttraumatic stress symptoms (PTSS) and depression, anxiety, resilience, Hemoglobin A1c (HbA1c), self-care behaviors, and diabetes-related distress among adolescents and young adults (AYA) with type 1 diabetes, a group navigating critical developmental transitions.MethodsFifty AYA, aged 14–25, from a pediatric diabetes unit of an urban academic medical center participated. Diabetes-related PTSS, mental health, resilience, and diabetes self-care were assessed using validated scales. Statistical analyses examined associations and predicted likelihoods of mental health difficulties based on PTSS severity.ResultsThe average HbA1c was 8.36% (SD = 1.76), with 74% exceeding the recommended level. About 30% exhibited clinically relevant diabetes-related PTSS. PTSS was positively correlated with depression (r = 0.367, p = 0.009), anxiety (r = 0.435, p = 0.002), and diabetes-related distress (r = 0.436, p = 0.002), and negatively correlated with resilience (r = -0.330, p = 0.019). Higher PTSS severity increased the odds of depression (OR = 1.08, p = 0.022) and anxiety (OR = 1.09, p = 0.009), while reducing resilience (OR = 0.931, p = 0.034).ConclusionAddressing both psychological and physical aspects of diabetes is essential. Integrating trauma-informed care and PTSS screening into routine management may improve outcomes and better support AYA during transitions. Given the study’s small sample and cross-sectional design, future longitudinal research is needed to confirm these findings.